5
$\begingroup$

I'd would like to know how to get the answer of the following problem:

$$\lim_{n \to \infty} \left(2\sqrt{n}\left(\sqrt{n+1}-\sqrt{n}\right)\right)^n$$

I know that the answer is $\frac{1}{e^{1/4}}$, but I can't figure out how to get there. This is a homework for my analysis class, but I can't solve it with any of the tricks we learned there.

This is what I got after a few steps, however it feels like this is a dead end:

$$\lim_{n \to \infty} \left(2\sqrt{n}\times \frac{\left(\sqrt{n+1}-\sqrt{n}\right)\times \left(\sqrt{n+1}+\sqrt{n}\right)}{\left(\sqrt{n+1}+\sqrt{n}\right)}\right)^n=$$ $$\lim_{n \to \infty} \left(\frac{2\sqrt{n}}{\sqrt{n+1}+\sqrt{n}}\right)^n$$

Thanks for your help in advance.

$\endgroup$
  • $\begingroup$ I suppose you meant "...as $\,n\to\infty\,$" , right? $\endgroup$ – DonAntonio Oct 7 '12 at 13:12
  • $\begingroup$ Yes, thanks for your input. $\endgroup$ – hegearon Oct 7 '12 at 13:15
  • $\begingroup$ Hint: What if you now divide num and den by the square root of n? Do you see a pattern in the result that you are familiar with? ~A $\endgroup$ – Amzoti Oct 7 '12 at 13:16
  • $\begingroup$ It could be simplified to $\frac{2^n}{\big(1+\sqrt{1+\frac{1}{n}}\big)^n}$ as well. $\endgroup$ – Nancy Rutkowskie Oct 7 '12 at 13:22
5
$\begingroup$

HINT: Use $$ \sqrt{n+1}-\sqrt{n} = \frac{\left(\sqrt{n+1}-\sqrt{n}\right) \left(\sqrt{n+1}=\sqrt{n}\right) }{\left(\sqrt{n+1}+\sqrt{n}\right) } = \frac{1}{\sqrt{n+1}+\sqrt{n}}$$ Now you limit becomes easier to handle: $$ \lim_{n \to \infty} \left(\frac{2 \sqrt{n}}{\sqrt{n+1} + \sqrt{n} }\right)^n = \lim_{n \to \infty} \left(1 - \frac{\sqrt{n+1} - \sqrt{n}}{\sqrt{n+1} + \sqrt{n} }\right)^n = \lim_{n \to \infty} \left(1 - \frac{1}{\left(\sqrt{n+1} + \sqrt{n}\right)^2 }\right)^n $$

$\endgroup$
3
$\begingroup$

Expanding the Taylor series of $\sqrt{1+x}$ near $x=0$ gives $ \sqrt{1+x} = 1 + \frac{x}{2} - \frac{x^2}{8} + \mathcal{O}(x^3).$ Thus $$ \left( 2\sqrt{n} ( \sqrt{n+1} - \sqrt{n} )\right)^n =2^n n^{\frac{n+1}{2}} \left(\sqrt{1+\frac{1}{n}}-1 \right)^n$$

$$=2^n n^{\frac{n+1}{2}} \left( \frac{1}{2n} - \frac{1}{8n^2}+ \mathcal{O}(1/n^3)\right)^n = n^{\frac{1-n}{2}} \left(1 - \frac{1}{4n} + \mathcal{O}(n^{-2})\right)^n\to e^{-1/4}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.